Think Modular: A Simple Apoferritin-Based Platform for the Multifaceted Detection of Pancreatic Cancer - Hwang, Mintai P.; Lee, Jong-Wook; Lee, Kyung Eun; Lee, Kwan Hyi (AMER CHEMICAL SOC, 2013)
The generation of nanosized probes often requires time-intensive and application-specific optimization processes that involve conjugating a nanoconstruct to a targeting moiety. Herein, we genetically modify apoferritin and generate a universal interface system composed of protein G and 6x His-tag. The resulting construct, conferred with modularity and high targeting efficiency, is applied toward two distinct applications in the detection of a pancreatic cancer biomarker and used to demonstrate its potential in the facile exchange of nanoprobe components.
Keywords: STREPTOCOCCAL PROTEIN-G; QUANTUM DOTS; CRYSTAL-STRUCTURE; TAGGED PROTEINS; FERRITIN GENES; IGG-BINDING; NANOPARTICLES; FRAGMENT; COMPLEX; BIOMARKERS